Risk factors of chronic kidney disease in cisplatin-based hyperthermia intraperitoneal chemotherapy - Chih-Chung Cheng; Hung-Chieh Yeh; Pei-Wen Su; Chien-Lin Ho; Sheng-Chi Chang (International Journal of Hyperthermia)
Purpose Cisplatin is commonly prescribed in hyperthermic intraperitoneal chemotherapy (HIPEC) for peritoneal malignancy. Acute kidney injury (AKI) is regarded as a common complication after HIPEC combined with cytoreductive surgery (CRS). However, post-HIPEC chronic kidney disease (CKD) is scarce and less investigated. This study aims to investigate the incidence of CKD following cisplatin-based HIPEC and to analyse the associated risk factors.Materials and Methods From January 2016 to August 2021, a total of 55 patients treated with CRS and cisplatin-based HIPEC for peritoneal carcinomatosis were categorized retrospectively into groups, with and without CKD. Demographics, comorbidity, surgery, postoperative management, and complications were collected to evaluate risk factors for cisplatin-based HIPEC-related CKD. Univariate and multivariate analyses were conducted to confirm the correlation between different variables and CKD occurrence.Results Of the 55 patients, 24 (43.6%) patients developed AKI and 17 (70.8%) patients of these AKI patients progressed to CKD. Multivariate regression analysis identified intraoperative use of parecoxib (Odds Ratio (OR) = 4.39) and intraoperative maximum temperature > 38.5°C (OR = 6.40) as major risk factors for cisplatin-based HIPEC-related CKD occurrence. Though type II diabetes mellitus and intraoperative complications were the independent risk factors of AKI following cisplatin-based HIPEC, but they were not shown in CKD analysis.Conclusion Intraoperative use of parecoxib during cisplatin-based HIPEC emerged as a significant risk factor for postoperative CKD. Clinicians should exercise caution in prescribing parecoxib during HIPEC procedures. Additionally, maintaining intraoperative body temperature below 38.5°C might be crucial to mitigate the risk of CKD development. This study underscores the importance of identifying and preventing specific risk factors to improve long-term renal outcomes in patients undergoing cisplatin-based HIPEC.